2022
DOI: 10.3390/jof8030311
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and Comparative Genomics Highlight Specific Genetic Features in Ganoderma Species

Abstract: The Ganoderma species in Polyporales are ecologically and economically relevant wood decayers used in traditional medicine, but their genomic traits are still poorly documented. In the present study, we carried out a phylogenomic and comparative genomic analyses to better understand the genetic blueprint of this fungal lineage. We investigated seven Ganoderma genomes, including three new genomes, G. australe, G. leucocontextum, and G. lingzhi. The size of the newly sequenced genomes ranged from 60.34 to 84.27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…It is believed that the genus Ganoderma encompasses more than 250 distinct species ( Wang et al, 2012 ; Kües et al, 2015 ; Jargalmaa et al, 2017 ; Sun et al, 2022c ). At present, the genomics and cultivation of Ganoderma genus are receiving increasing attention, promoting the development and utilization of Ganoderma resources ( Si et al, 2021 ; Sun et al, 2022b ). It has been observed that some species from the Ganoderma genus can be detrimental to woody plants, such as G .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the genus Ganoderma encompasses more than 250 distinct species ( Wang et al, 2012 ; Kües et al, 2015 ; Jargalmaa et al, 2017 ; Sun et al, 2022c ). At present, the genomics and cultivation of Ganoderma genus are receiving increasing attention, promoting the development and utilization of Ganoderma resources ( Si et al, 2021 ; Sun et al, 2022b ). It has been observed that some species from the Ganoderma genus can be detrimental to woody plants, such as G .…”
Section: Introductionmentioning
confidence: 99%
“…2020 ). Currently, 18 species have been included in the genus Sanguinoderma worldwide ( Sun, Lebreton, et al 2022 ). Among them, Sanguinoderma infundibulare B.K.…”
Section: Introductionmentioning
confidence: 99%
“…With the reduction of genome sequencing costs and the rapidly increasing numbers of fungal genome data, more studies have focused on the innovation and evolution of fungal life modes using omics data analyses ( Floudas et al 2012 ; Sipos et al 2017 ; Naranjo-Ortiz and Gabaldón 2019 ; Lebreton et al 2021 ; Lofgren et al 2021 ; Sun et al 2022 ; Wu et al 2022c ). Comparative genomic analyses have suggested that white rot fungi differ from brown rot fungi by their CAZymes repertoire ( Floudas et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%